2012
DOI: 10.1073/pnas.1109457109
|View full text |Cite
|
Sign up to set email alerts
|

Essential requirement for β-arrestin2 in mouse intestinal tumors with elevated Wnt signaling

Abstract: β-Arrestins (Arrb) participate in the regulation of multiple signaling pathways, including Wnt/β-catenin, the major actor in human colorectal cancer initiation. To better understand the roles of Arrb in intestinal tumorigenesis, a reverse genetic approach (Arrb −/− ) and in vivo siRNA treatment were used in Apc Δ14/+ mice. Mice with Arrb2 depletion (knockout and siRNA) developed only 33% of the tumors detected in their Arrb2-WT littermates, whereas Arrb1 depletion remained without significant effect. These rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…2D). Adding credence to the analysis, the major functions identified are consistent with the in vitro characterization of (D-Trp 12 ,Tyr 34 )-bPTH(7-34) actions in primary calvarial osteoblasts (Gesty-Palmer et al, 2013) and data emerging from the cancer field suggesting that arrestins function as regulators of tumor cell proliferation, survival, and metastasis (Buchanan et al, 2006;Dasgupta et al, 2006;Moussa et al, 2008;Chun et al, 2009;Lakshmikanthan et al, 2009;Li et al, 2009;Rosanò et al, 2009;Liu et al, 2011;Bonnans et al, 2012;Fereshteh et al, 2012).…”
Section: Understanding Bias At a Systems Levelmentioning
confidence: 66%
“…2D). Adding credence to the analysis, the major functions identified are consistent with the in vitro characterization of (D-Trp 12 ,Tyr 34 )-bPTH(7-34) actions in primary calvarial osteoblasts (Gesty-Palmer et al, 2013) and data emerging from the cancer field suggesting that arrestins function as regulators of tumor cell proliferation, survival, and metastasis (Buchanan et al, 2006;Dasgupta et al, 2006;Moussa et al, 2008;Chun et al, 2009;Lakshmikanthan et al, 2009;Li et al, 2009;Rosanò et al, 2009;Liu et al, 2011;Bonnans et al, 2012;Fereshteh et al, 2012).…”
Section: Understanding Bias At a Systems Levelmentioning
confidence: 66%
“…These data suggest that ARRB1, but not ARRB2, plays an essential role in inflammationinduced hepatocellular carcinogenesis. It was reported that ARRB2, but not ARRB1, is essential for the initiation and growth of intestinal tumours 37 . Thus far, ARRB1 and ARRB2 have been found to have different effects in initiation and development of malignant tumours 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a previous report determined that DVL2 loss protects against tumor development by reducing Wnt signaling in Apc min/+ ; Dvl2 ΔIEC mice (51), suggesting a nonredundant function of DVL2 for tumorigenesis in Apc min/+ mice. In addition, we noticed that several Wnt regulators, including WNK2, LKB1, β-arrestin 2, and RAF1, were altered in the absence of SETD2 (52)(53)(54)(55). For instance, β-arrestin 2 is essential for the initiation and growth of intestinal tumors displaying elevated Wnt pathway activity in Apc-mutated mice (54), and WNK2 also stimulates the Wnt signal through regulation of β-catenin stability (52).…”
Section: Methodsmentioning
confidence: 97%
“…In addition, we noticed that several Wnt regulators, including WNK2, LKB1, β-arrestin 2, and RAF1, were altered in the absence of SETD2 (52)(53)(54)(55). For instance, β-arrestin 2 is essential for the initiation and growth of intestinal tumors displaying elevated Wnt pathway activity in Apc-mutated mice (54), and WNK2 also stimulates the Wnt signal through regulation of β-catenin stability (52). Thus, we cannot completely rule out the possibility that, in addition to our findings, SETD2 might also act on different Wnt pathway components to finetune Wnt signals during intestinal regeneration and tumorigenesis.…”
Section: Methodsmentioning
confidence: 99%